The Types Of Corrective Feedback Implemented By The Teacher In Teaching Writing Descriptive Text To The Second Year Students Of SMP N 2 Baturetno - Arifah, Meitasari Nur, Aryati Prasetyarini, M.Pd, Siti Fatimah, S.Pd,. M.Hum (2016)
This study is aimed at describing: 1) the types of the corrective teacher feedback used in teaching descriptive text, 2) the student's response of the feedback given by the teacher in teaching writing descriptive text. In achieving the objectives, the researcher used descriptive qualitative as the approach to collect and analyze the data. The research was held in SMP N 2Baturetno. The research took 30 students of the second year students as the subject of the study. The writer get the data of the research from event, informants, and document. The techniques of collecting data are the observation and interview about the writing teaching- learning process. The result of the analysis shows that the teacher used three types of corrective feedback, namely feedback on content (positive feedback), feedback on form (negative feedback) and the use of red ink and black ink in corrective feedback. The writer can conclude, when the teacher gives direct feedback to the students make easily to understand the learning and they can know what their mistakes. They said that the feedback type applied by the teacher in the teaching writing descriptive makes them easy to write and they can identify and correct the errors. The teacher also used of ink color to correction the learning. In the observation, the teacher uses the redink when she correct students work.In teacher corrective feedback, students can know and correct the errors after it is corrected by the teacher. Keywords: teacher corrective feedback type, descriptive text